Learning Engagement In The Light of Goal Orientations and Academic Delay of Gratification of Health colleges students - Nourah ALGadheeb (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The current study aimed to know the relationship between the learning engagement and the goal orientations and the academic delay of gratification of the students of the Health colleges students at Princess Nourah bint Abdulrahman University, and the study aimed at predicting the engagement learning through the study variables. The study sample consisted of (359) students selected randomly from the Health colleges at Princess Nourah bint Abdulrahman University, and three Scales were used learning engagement, goal orientations and the academic delay of gratification, were tested for validity and reliability. Means, standard deviation, percentages, Pearson correlation, and regression were used in analyzing data. The results revealed that the level of learning engagement was higher than average, the average of the highest cognitive engagement of the sample, then emotional engagement, finally behavioral engagement, the study sample adopted 69.9% mastery goals, then performance-avoidance 16.2%, and then performance-approach 4.2%. The sample showed a high level of Academic delay of gratification. On the relationship between variables, the results showed a positive relationship between engagement learning, mastery goals and performance-approach, lack of relationship with performance-avoidance, and a positive relationship with delay of gratification. There is also a positive relationship between the academic delay of gratification and the mastery goals, and the absence of a relationship between academic delay of gratification and performance both types avoidance and approach, and the study revealed that engagement learning can be predicted through mastery goals and performance-approach by (28.8 %).